APPLICATION VIRTUAL CAMPUZ PLAN STMIK JAKARTA STI&K USING MACROMEDIA FLASH MX PROFESSIONAL 2004 - Aryo Budisatrio (Jurnal Sistem Informasi, 2007)
The development of computerized technology in the current increasingly with the internet boom in information technology. Through this internet much information can be found in various forms of both images and text. Through this Internet technology STMIK Jakarta STI & K can provide more information about the facility as well as other information. One of them is information about the facilities available in campus buildings STMIK Jakarta STI & K.